Polygamy, Nusyuz, and Ila’, and the Role of Judges in Resolving Marriage Issues - Auziah, Silfia; Ningsih, Rahayu; Arifin, Zainul; K, Munawir (Suluah Pasaman, 2025)
In the reality of married life between husband and wife, there are usually both good and bad consequences, such as polygamy in marriage, which is when a man has more than one wife.  From an Islamic legal perspective, polygamy is limited to only four wives. Polygamy has existed throughout human history, so it is not a trend that has emerged suddenly. Islamic law regulates polygamy for those who meet the requirements to practice it. However, many current practices of polygamy do not comply with Islamic law, falling far short of what is expected. Marital conflicts often cause arguments and heated debates, and physical and psychological violence is not uncommon, which can disrupt the harmony of the husband and wife's relationship and give rise to what is commonly known as nusyuz (disobedience). Then there is ila', which is the husband's vow not to have sexual relations with his wife for a certain period of time, and the role of the judge in resolving marital problems. The purpose of this study is to explain the requirements for polygamy according to Islam, such as nusyuz, ila, and the role of the judge in marriage. This article will serve as a guide for us in overcoming various problems in marriage.